Managing Anxiety from Cancer (MAC): A pilot randomized controlled trial of an anxiety intervention for older adults with cancer and their caregivers. Issue 2 (April 2021) - Trevino, Kelly M.; Stern, Amy; Hershkowitz, Robin; Kim, Soo Young; Li, Yuelin; Lachs, Mark; Prigerson, Holly G.
Abstract: Objective: Anxiety is common in older adults with cancer (OACs) and their caregivers and is associated with poor outcomes including worse physical symptoms, poor treatment adherence and response, and longer hospitalizations. This study examined the feasibility, acceptability, adherence, and preliminary efficacy of a cognitive-behavioral therapy (CBT) intervention for OACs and their caregivers. Method: Patients with active cancer age 65 years and older and their caregivers were randomized to Managing Anxiety from Cancer (MAC), a seven-session CBT-based psychotherapy intervention delivered over the telephone or usual care. Patients and caregivers completed the intervention separately with licensed social workers. Self-report measures of anxiety, depression, and quality of life were administered after randomization and following intervention completion. Analyses were conducted separately for patients and caregivers and at the dyad level. Hierarchical Linear Modeling accounted for the within-dyad intraclass correlation coefficients (ICCs) by random intercepts associated with the dyads. Results: Twenty-nine dyads were randomized; 28 (96.6%) patients and 26 (89.7%) caregivers completed all study procedures. Of dyads randomized to MAC, 85.7% ( n = 12) of patients and caregivers completed all seven sessions. Most patients (≥50%) and over 80% of caregivers rated the overall intervention and intervention components as "moderately" to "very" helpful. MAC was associated with a greater reduction in anxiety among dyads than usual care, the effect of MAC was greater in caregivers than in patients, and improvement in patient anxiety was associated with the reduction in caregiver anxiety. However, these results did not reach statistical significance. Significance of results: This pilot study demonstrates the feasibility of MAC and suggests strategies for improving acceptability, with a focus on adherence. Furthermore, these results indicate that MAC is promising for the reduction of anxiety in OAC–caregiver dyads and may be particularly beneficial for OAC caregivers. Larger randomized controlled trials are needed to evaluate the efficacy of MAC.